Respuesta :
Answer:
-60 - 54v or -60 + (-54v)
Step-by-step explanation:
If you choose to expand this equation to make it easier, you can write it out as (-6 × 10) + (-6 × 9v). With this, you can simplify this to -60 + (-54v).
hello!
===========================================================
In order to simplify this expression, we need to use the distributive property, which states:-
[tex]\bigstar{\underline{\boxed{\pmb{a(b+c)=ab+ac}}}\longleftarrow\sf{the~distributive~property}[/tex]
Where:-
[tex]\maltese[/tex] we distribute a by multiplying it times b and c
Now, let's use this property to simplify our expression:-
[tex]\longrightarrow\sf{-6(10+9v)}[/tex]
[tex]\longrightarrow\sf{-60-54v}[/tex]
==========================================================
note:-
Hope everything is clear; if you need any clarification/explanation, kindly let me know, and I'll comment and/or edit my answer :)